The Effect of Government Spending on Education, Health and Social Protection Sectors Towards the Human Development Index in Central Kalimantan - Mailassa’adah Mailassa’adah; Pudjihardjo Pudjihardjo; Umar Burhan (e-2477-1929)
Education and health are became the main capitals that must be owned by a nation to improve its potency. In addition to education and health, social protection is a policy that designed by the government in order to finance all kinds of efforts that purposed to assist citizens who have social problems to become capable in fulfilling their basic needs. This study aims to determine the effect of government expenditure eon education, health and social protection sectors towards the Human Development Index, and what sector that most influential to the HDI among those three. The results of this study showed a positive and significant impact in all sectors particularly for the government spending on the education sector as the most influential one. This study uses a quantitative approach, the characteristics of the data and information used by researchers in this study are macro in nature, so the quantitative approach is relevant to this research.